Identification of Key Residues for the Binding of Glucagon to the N-Terminal Domain of its Receptor: An Alanine Scan and Modeling Study - Prévost, M.; Vertongen, P.; Waelbroeck, M. (Hormone and Metabolic Research, 2012)
Glucagon plays an essential role in the glycemia maintenance during fasting, but also aggravates hyperglycemia in diabetic patients. A series of analogues of glucagon were synthesized replacing each amino acid of the C-terminal region (residues 15–29) with alanine. The residues affecting the binding to the glucagon receptor are found to be located on one face of the glucagon helix. Several 3-dimensional models of the N-terminal domain of the glucagon receptor in complex with its ligand peptide were built and used to analyze the peptide-receptor interface in terms of the nature of the peptide residues and the interactions they form with the receptor. The models suggest that glucagon keeps its native helical structure upon binding, and that a large part of the interface formed with the receptor is hydrophobic. We find that in the C-terminal region, F22, V23, M27, and D15 are the most important residues for peptide binding. They bury a large portion of their solvent accessible surface area and make numerous interactions with the receptor mainly of the hydrophobic type.
Keywords: class B receptor; ligand docking; receptor recognition; binding site